2016
DOI: 10.3390/su8101019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Acequia Irrigation Systems Using System Dynamics: Model Development, Evaluation, and Sensitivity Analyses to Investigate Effects of Socio-Economic and Biophysical Feedbacks

Abstract: Agriculture-based irrigation communities of northern New Mexico have survived for centuries despite the arid environment in which they reside. These irrigation communities are threatened by regional population growth, urbanization, a changing demographic profile, economic development, climate change, and other factors. Within this context, we investigated the extent to which community resource management practices centering on shared resources (e.g., water for agricultural in the floodplains and grazing resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 40 publications
5
42
0
2
Order By: Relevance
“…Sensitivity analyses revealed that agricultural profitability, community make-up (i.e., percentage of residents with historical familial ties), and land use (residential vs. cultivated) were key determinants of irrigation system response. This was due to their influence on feedback processes responding to input parameter perturbations [75]. Their results correspond well with other types of system analysis efforts in the field of socio-hydrology [82].…”
Section: Hydrology and Water Resource Managementsupporting
confidence: 84%
See 3 more Smart Citations
“…Sensitivity analyses revealed that agricultural profitability, community make-up (i.e., percentage of residents with historical familial ties), and land use (residential vs. cultivated) were key determinants of irrigation system response. This was due to their influence on feedback processes responding to input parameter perturbations [75]. Their results correspond well with other types of system analysis efforts in the field of socio-hydrology [82].…”
Section: Hydrology and Water Resource Managementsupporting
confidence: 84%
“…Similar to SD applications in water resource planning, water resource problem analyses (i.e., testing changing conditions or alternative policies) have had widespread application in the literature [55,[66][67][68][69][70][71][72][73][74][75] as well as in the System Dynamics Society [76][77][78][79][80][81] across a broad range of issues from energy production to agriculture to municipal water management. We highlight two cases, one dealing with sensitivity analyses of uncertain socioeconomic parameters in a traditional irrigation community in northern New Mexico, USA [75], and another on scenario analyses of alternative water transfer policies in the Zayandeh-Rud River Basin of Iran [72].…”
Section: Hydrology and Water Resource Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…His success in analyzing industrial business cycles extended the use of system dynamics to other fields, like urban problems (Forrester 1969) and global problems (Meadows et al 1972, 1974, Forrester 1973. System dynamic modeling has proved particularly useful for studying complex systems like SESs (Roberts et al 1983, Costanza and Ruth 1998, Martínez-Fernández et al 2000, Pérez et al 2012, Banos-Gonzalez et al 2015, Turner et al 2016.…”
Section: Methodsmentioning
confidence: 99%